1998
DOI: 10.2307/176702
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Preferences of a Generalist Salt-Marsh Crab: Relative Importance of Multiple Plant Traits

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Few studies have evaluated the relative importance of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 40 publications
(81 reference statements)
2
29
1
Order By: Relevance
“…Our results strengthen the findings from a previous study which showed that leaf structural defences are the primary factor in determining the feeding choices of P. lividus between inflorescences and leaves, whereas nutrient content and secondary chemistry are of secondary importance (Vergés et al 2007b). These findings concur with numerous studies that show structural defences to be of paramount importance in mediating the feeding preferences of a wide range of terrestrial and aquatic herbivores (Coley 1983;Pennings et al 1998;Lucas et al 2000;Hanley et al 2007). …”
Section: Discussionsupporting
confidence: 92%
“…Our results strengthen the findings from a previous study which showed that leaf structural defences are the primary factor in determining the feeding choices of P. lividus between inflorescences and leaves, whereas nutrient content and secondary chemistry are of secondary importance (Vergés et al 2007b). These findings concur with numerous studies that show structural defences to be of paramount importance in mediating the feeding preferences of a wide range of terrestrial and aquatic herbivores (Coley 1983;Pennings et al 1998;Lucas et al 2000;Hanley et al 2007). …”
Section: Discussionsupporting
confidence: 92%
“…Plants experiencing salt stress commonly increase tissue concentrations of salts and/or nitrogen-based osmotica (Flowers et al 1977(Flowers et al , 1986Rozema et al 1985). Salt in food stimulates feeding by Armases (Pennings et al 1998), likely explaining the preference of this crab for plants from the high end of the salinity gradient. Most herbivores would be expected to prefer foods with higher nitrogen content (White 1984), but this may have been partially counterbalanced in the case of insects by higher salt levels and/or by other changes in plants growing in high-salinity soils.…”
Section: Discussionmentioning
confidence: 99%
“…Litter quality C:N ratios of plants have been utilized as measures of litter quality (Sterner and Elser 2002;Pennings et al 1998). To measure C and N content, fresh leaf material from nonsenescent tamarisk and several native plants (S. pacifica, Juncus acutus, J. cornosa) in each block (n = 4) was collected from the study site, rinsed with Milli-Q Ò water, placed in pre-combusted vials or tin boats, dried at 65°C, and kept in a desiccator until analysis.…”
Section: Leaf Turnover Calculationsmentioning
confidence: 99%